The investment writing handbook : how to craft effective communications to investors - Kedem, Assaf, 1973- (John Wiley & Sons, Inc., 2018)
Providing practical, accessible guidance for crafting more effective investor communications, this book explains the principles and conventions that help writing achieve its purpose and offers clear explanations to help you transform your communication strategy, execution, and results. --